2021
DOI: 10.31223/x59g7p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Episodicity and Migration of Low Frequency Earthquakes modeled with Fast Fluid Pressure Transients in the Permeable Subduction Interface

Abstract: In many subduction zones, the plate interface hosts intermittent, low-frequency, low-magnitude seismic tremor and low-frequency earthquakes (LFEs). Seismic activity clusters in episodic bursts that migrate along the fault zone in complex ways. Geological structures in fossil tremor source regions testify to large and pervasive variations of fluid pressure and permeability. Here, we explore the potential of fluid pressure transients in a permeable subduction interface to trigger seismic sources and induce inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 94 publications
2
4
0
Order By: Relevance
“…2, C and D). The modeling shows that in a conduit with background diffusivity of ∼100 m 2 s −1 [as previously inferred for the KVG (22)], rapid migration velocities can reach ∼10 km/hour (53), which is again close to the observations presented here.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2, C and D). The modeling shows that in a conduit with background diffusivity of ∼100 m 2 s −1 [as previously inferred for the KVG (22)], rapid migration velocities can reach ∼10 km/hour (53), which is again close to the observations presented here.…”
Section: Discussionsupporting
confidence: 89%
“…In a conduit with multiple low permeability barriers, the overall permeability is proportional to the number of open versus closed valves ( 45 ), which, on average, increases with overall pressure gradient across the system. A recent study of dynamics of such a system ( 53 ) has shown that closely located valves can interact, which results in cascades forming very rapidly migrating pressure transients (analogous to nonlinear pressure waves) able to propagate in both upward and downward directions, similar to what we observe for the KVG tremors (Fig. 2, C and D).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The tremor episodes that we identified began near and downdip from the subducted seamount (except for the 2016 episode, which was induced by an M JMA 6.5 earthquake), thus suggesting that the seamount played the role of the valve in the model of Farge et al. (2021). Note that the triggering of a tremor according to the valve model of Farge et al.…”
Section: Discussionmentioning
confidence: 64%
“…Farge et al. (2021) suggested a model in which episodic activity and migration of tremor at a plate boundary was the result of a fluid valve mechanism that involves fluid clogging in regions of low permeability, which increases pore pressure. When that pore pressure reaches a threshold value, an impulsive unclogging event occurs that opens the valve and generates a rapid pressure transition accompanied by tremors.…”
Section: Discussionmentioning
confidence: 99%